2005
DOI: 10.1210/en.2004-1116
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pharmacokinetics of 1α,25-Dihydroxyvitamin D3and 25-Hydroxyvitamin D3in the Blood and Tissues of the 25-Hydroxyvitamin D-24-Hydroxylase (Cyp24a1) Null Mouse

Abstract: The 25-hydroxyvitamin D-24-hydroxylase (CYP24A1) plays an important role in regulating concentrations of both the precursor 25-hydroxyvitamin D3 [25(OH)D3] and the hormone 1alpha,25-dihydroxyvitamin D3 [1alpha,25(OH)(2)D3]. Previous studies suggest that Cyp24a1-null mice cannot clear exogenous 1alpha,25(OH)2D3 efficiently. Here, we examined the metabolic clearance in Cyp24a1-null mice in vivo and in vitro using a physiological dose of [1beta-3H]1alpha,25(OH)2D3 or [26,27-methyl-3H]25(OH)D3. Cyp24a1-null mice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
81
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 36 publications
10
81
0
2
Order By: Relevance
“…vitro studies collectively showed that calcitroic acid and 1␣,25-(OH) 2 D 3 -26,23-lactone are both 1␣,25-(OH) 2 D 3 -induced products, both result from recombinant CYP24A1 action, and both are absent in VDR-null and CYP24A1-null mice in vivo (8,9). These products are physiologically different because the calcitroic acid is a rapidly cleared catabolite with no discernible biological activity and 1␣,25-(OH) 2 D 3 -26,23-lactone belongs to a family of known VDR antagonists (14,15) with better vitamin D-binding protein-binding properties and greater metabolic stability (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vitro studies collectively showed that calcitroic acid and 1␣,25-(OH) 2 D 3 -26,23-lactone are both 1␣,25-(OH) 2 D 3 -induced products, both result from recombinant CYP24A1 action, and both are absent in VDR-null and CYP24A1-null mice in vivo (8,9). These products are physiologically different because the calcitroic acid is a rapidly cleared catabolite with no discernible biological activity and 1␣,25-(OH) 2 D 3 -26,23-lactone belongs to a family of known VDR antagonists (14,15) with better vitamin D-binding protein-binding properties and greater metabolic stability (26).…”
Section: Discussionmentioning
confidence: 99%
“…1). Studies using CYP24A1-knockout (8) and VDR-knockout mice (8,9) demonstrate the total absence of calcitroic acid and 1␣,25-(OH) 2 D 3 -26,23-lactone formation when the vitamin Dinducible, VDR-mediated CYP24A1 is not expressed. The in vivo result of CYP24A1 ablation is decreased viability, with 50% of mice not surviving beyond weaning because of hypercalcemia and nephrocalcinosis (8,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyp24a1 KO mice develop hypercalcemia, and 50% of the homozygous mutants die before 3 weeks of age probably due to severe hypercalcemia. The animals surviving to adulthood are fertile despite deposition of mineral in several organs of the mutant mice (Masuda et al 2005). A more detailed evaluation of testis histology and reproductive phenotype were also performed in males from the Tokyo Vdr KO strain, revealing an increased luminal diameter and shortened epithelial width in some tubules from 10-week-old Vdr KO mice compared with controls (Kinuta et al 2000).…”
Section: Vd Regulates Biosynthesis Of Estradiol and Testosteronementioning
confidence: 99%
“…To prevent the excessive accumulation of 1,25(OH) 2 D 3 and its toxic hypercalcemic effects, CYP24 expression is up-regulated by 1,25(OH) 2 D 3 in a negative feedback mechanism (8). CYP24 also catalyzes the removal of 25(OH)D 3 from the body (9).…”
Section: Introductionmentioning
confidence: 99%